2016
DOI: 10.1016/j.neuroscience.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin system in autism spectrum disorder: From biomarker to animal models

Abstract: Elevated whole blood serotonin, or hyperserotonemia, was the first biomarker identified in autism spectrum disorder (ASD) and is present in more than 25% of affected children. The serotonin system is a logical candidate for involvement in ASD due to its pleiotropic role across multiple brain systems both dynamically and across development. Tantalizing clues connect this peripheral biomarker with changes in brain and behavior in ASD, but the contribution of the serotonin system to ASD pathophysiology remains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
328
2
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 418 publications
(347 citation statements)
references
References 229 publications
(267 reference statements)
12
328
2
5
Order By: Relevance
“…In the present study, the levels of both serotonin and its transporter were measured and compared with age- and gender-matched control subjects, and a significant increase in the levels of serotonin and SERT was observed in autistic patients. The results of this study were in consistent with those obtained from previous researches that demonstrate a significant elevation in the levels of serum serotonin in autistic children in a comparison with control subjects and assumed that serotonin may have an important role in the autistic symptoms 2,17. In studies conducted previously, hyperserotonemia was consistently reported in 22-29% of patients suffering from ASD that makes serotonin considered as the best-characterized autistic biomarker 16.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the levels of both serotonin and its transporter were measured and compared with age- and gender-matched control subjects, and a significant increase in the levels of serotonin and SERT was observed in autistic patients. The results of this study were in consistent with those obtained from previous researches that demonstrate a significant elevation in the levels of serum serotonin in autistic children in a comparison with control subjects and assumed that serotonin may have an important role in the autistic symptoms 2,17. In studies conducted previously, hyperserotonemia was consistently reported in 22-29% of patients suffering from ASD that makes serotonin considered as the best-characterized autistic biomarker 16.…”
Section: Discussionsupporting
confidence: 92%
“…In studies conducted previously, hyperserotonemia was consistently reported in 22-29% of patients suffering from ASD that makes serotonin considered as the best-characterized autistic biomarker 16. Hyperserotonemia in autistic patients are seemingly owned to the excessive accumulation of serotonin within the platelets, whereas the level of free serotonin were not affected 17,18. The uptake of 5-HT into platelets is mediated by serotonin transporter similar to that expressed in neurons 19.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As it is difficult, if not otherwise impossible to recapitulate all aspects of neuropsychiatric disorders, animal models are limited in the range of symptoms that they attempt to reflect, and, depending on the procedures used to induce pathological behaviours, tap into circumscribed presumed physiological mechanisms underlying those behaviours. Animal models are composed of procedures used to induce abnormal psychiatric-like behaviours in an otherwise healthy and "normal" animal (Geyer and Markou, 2002;McArthur and Borsini, 2006), the results of which are again measured by not only behaviourally, but also by physiological procedures such as biochemical (Muller et al, 2016), electrophysiological (Braff and Geyer, 1990), genetic (Gould and Manji, 2004), neurological (Beal, 2001), or imaging procedures (King et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the large number of potential targets resulting from the explosion of genomics and related scientific disciplines suggests that identifying the various biology associated with the different presentations of autism is critical in order to stratify individuals in subgroups with shared common biology likely to respond to a particular agent, as per the principles of precision medicine (Loth et al, 2016). Current evidence suggests that manipulation of excitation-to-inhibition (E:I) balance and neuropeptide targets may be promising candidates.Altered signal-to-noise ratio due to E:I balance alteration has been proposed as a potential biological common pathway in at least a subgroup of autistic individuals Altered serotonin mechanisms and increased serotonin blood levels have been reported in subgroups in the autistic population; reciprocal interactions between serotonin and other neuropeptides, including oxytocin, may be particularly important for social behaviour (Muller et al, 2016). A large RCT of buspirone in the 2-6 year-old population showed no difference in the total ADOS score but reduction in the restricted and repetitive behaviour score on 2.5 mg daily (Chugani et al, 2016).…”
mentioning
confidence: 99%